2008
DOI: 10.1080/10425170701574920
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and comparative bioinformatic analysis of feline glucose-6-phosphatase catalytic subunit cDNA

Abstract: Glucose-6-phosphatase is a multicomponent enzyme composed of a transporter subunit and a catalytic subunit that is involved in hepatic glucose production. The objective of the present study was to determine the complete nucleotide sequence of feline hepatic glucose-6-phosphatase catalytic subunit (G6Pc) cDNA and to perform comparative analysis of the molecular features of the feline G6Pc cDNA and protein. Feline G6Pc cDNA contains 2261 bases and encodes a 357 aa protein. The feline cDNA and protein are highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Percent (%) nucleotide identity is highest with pancreatic GK cDNAs from primates (>90%) and slightly less with rodent pancreatic GK cDNAs. The latter finding is consistent with a trend observed in other feline genes involved in carbohydrate metabolism, such as G6PC (glucose-6-phosphatase catalytic subunit) [13] and KHK (ketohexokinase) [14], which have shown greater nucleotide identity with primate and canine sequences than with rodent species. The ten putative exons identified in feline GK have homology with established exon sequences of human pancreatic GK.…”
Section: Discussionsupporting
confidence: 88%
“…Percent (%) nucleotide identity is highest with pancreatic GK cDNAs from primates (>90%) and slightly less with rodent pancreatic GK cDNAs. The latter finding is consistent with a trend observed in other feline genes involved in carbohydrate metabolism, such as G6PC (glucose-6-phosphatase catalytic subunit) [13] and KHK (ketohexokinase) [14], which have shown greater nucleotide identity with primate and canine sequences than with rodent species. The ten putative exons identified in feline GK have homology with established exon sequences of human pancreatic GK.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the need for a high gluconeogenic capacity, the activity of the glucose-6-phosphatase (G6Pase) enzyme system is comparatively high in feline liver compared to canine liver (Washizu et al 1999;Tanaka et al 2005). Molecular analysis of feline G6Pase indicates it is highly conserved at the level of mRNA and protein, suggesting that the high G6Pase activity that characterizes feline hepatic metabolism results from changes in gene expression rather than species-specific regulation of the G6Pase enzyme (Lindbloom et al 2008). Likewise, species-specific differences in hepatic gene expression may explain the comparatively low capacity for glucose phorphorylation previously observed in feline liver.…”
Section: Introductionmentioning
confidence: 76%
“…Although feline genes involved in glucose metabolism appear to be highly conserved (7981), work in cats has clearly demonstrated that the molecular basis of feline hepatic glucose-sensing differs from the model defined in the non-carnivore liver (82). GCK and GCKR (the gene that encodes GKRP) mRNAs are absent from feline liver and activities of GCK and GKRP proteins are not detectable (35, 38, 82).…”
Section: Carnivore Hepatic Glucose-sensing Pathwaysmentioning
confidence: 99%